A revision of the Rhododendron taipaoense complex (subg. Tsutsusi sect. Tsutsusi, Ericaceae), based on observations of morphological characters and seed micromorphology - Jin, Xiao-Feng; Ding, Bing-Yang; Zhou, Ying-Ying; Jin, Shui-Hu; Yang, Wang-Wei (Phytotaxa, 2013)
In this paper, we present a revision of the Rhododenron taipaoense complex, including R. taipaoense and eight other named species, based on literature survey, field collections and observations, inspection of herbarium specimens, statistical analysis of morphological characters, and SEM observation of seed shape and testa. We evaluated all characters that have previously been used to diagnose these species: indumentum of young shoots and abaxial surfaces of leaves; filament dimensions; style base; leaf color, size, and apex shape; flower number per inflorescence; corolla length; and length of the stamen and pistil. Cluster analysis of 146 individuals showed that individuals from different populations are interdigitated, irrespective of traditional taxonomic limits. Analysis of morphological data using principal coordinate analysis (PCoA) likewise shows a continual gradation between populations, rather than disjunctures between named species. Consequently, only one species is recognized in the present paper, and R. apricum, R. falcinellum (R. apricum var. falcinellum), R. florulentum, R. hepticum, R. piceum, R. rufulum, R. spadiceum, and R. rufoindumentum (nom. nud.) are all reduced to synonyms of R. taipaoense.